INVESTIGATING FACTORS ENHANCING INTERCULTURAL COMMUNICATION: FROM STUDENTS’ WRITING TO TEACHERS’ PRACTICE - Papadopoulos, Isaak (The Modern Higher Education Review, 2019)
Intercultural communication constitutes a research field with an increasing interest within the Greek context, as the Greek classes are characterized to a great extent by a cultural- and linguistic- diversity. This study aims at investigating linguistic-elements used by students as a key-factor affecting intercultural written communication between Greek students and students coming from other countries. Effectiveness in intercultural communication is a multifaceted factor which is dependent both on the use of intercultural communication strategies and on the way that speakers/writers modify their utterances in terms of either softening or intensifying their speech as well. More specifically, through this research attempt was made to record internal modifiers, linguistic elements which act either as downgraders (mitigators), aiming to soften the act or as upgraders aiming to intensify the coerciveness or urgency of the act performed by the speakers. Towards that goal, a subject of 150 students (11-12 years of age) was urged to influence a pen-friend from another cultural environment, as regards to taking up a new sports-activity while the scripts of the students underwent investigatory qualitative research. Following the qualitative analysis of the students’ pieces of writing, it was revealed that students made an extensive use of a) downgraders like the marker ’please’, consultative devices and subjectivisers as well as b) upgraders such as overstaters and time intensifiers. With respect to the fact that employing modification within the context of social interaction among people from different cultural backgrounds is of utmost importance, it is necessary the students to get familiarized with the significance of modification in their discourse and be encouraged to make use of modifiers which empower their communication within and outside the school context.